The Effectiveness of Da'wah on Social Media on Oki Setiana Dewi's Youtube Account - Diah Hani (Kawakib: Journal of Multidisciplinary Research, 2024)
Technological developments in today's digital era mean that everyone can access social media quickly. This social media is a media that is used as the biggest source of information for the public to find out their curiosity, one of which is YouTube media. YouTube is a platform where it is possible to upload and share videos. YouTube has also become a global phenomenon. Based on this phenomenon, it turns out that YouTube has been widely used as a medium for preaching for Muslims, especially Ustadzah Oki Setiana Dewi in conveying Islamic studies through videos. If a preacher uses YouTube with his lecture recorded using a camera and then uploaded, it will attract a lot of public attention. The preaching uploaded by Ustadzah Oki Setiana Dewi via the YouTube platform on the OSD Official channel account, has attracted the attention of the public. This problem is whether the preaching delivered by Oki Setiana Dewi via the YouTube platform is effective and can attract the public's attention. The aim is to see the effectiveness of the preaching delivered by Oki Setiana Dewi via YouTube.